Analisis Kesesuaian Konstitusi Ekonomi Indonesia Terhadap Ekonomi Islam - Rama, Ali; Makhlani, Makhlani (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2014)
The Similarities of Indonesian Economy Constitution to Islamic Economy. This study invistigates the similarities between the constitution of the Indonesian economy and Islamic economic system. It finds that the constitution of Indonesian economy have in common with the Islamic economic system, especially at the basic values, basic principles and instrumentals. The main similarities lie in the principle of economic activities based on the principles of solidarity and togatherness and the role of the state in the allocation of economic resources for economic prosperity and welfare of the whole people. Another important similarity is the presence of high concern towards the needy and neglected children through various economic policy instruments such as social security and social protection programs. Therefore, it is no longger relevant to polarize between the Indonesian economic constitution or Pancasila economic system and Islamic economic system DOI:10.15408/aiq.v6i1.1367